Analisis Perbedaan Unsur Penyalahgunaan Kewenangan dalam Undang-Undang Tipikor dan Undang-Undang Administrasi Pemerintahan: Implikasi terhadap Penegakan Hukum - Very Pahala Sijabat; Zico Ricardo Aritonang; Lenny Maria Aritonang; Agatha Christie Tarigan (Jurnal Hukum Lex Generalis, 2024)
Abuse of authority is an important issue in criminal and administrative law in Indonesia. This study discusses the differences in elements of abuse of authority in the Corruption Law and the State Administration Law and their impact on law enforcement. The results of the analysis show that the differences in approach in the two laws have the potential to cause legal uncertainty and overlapping authority. Regulation harmonization is needed to ensure the effectiveness of law enforcement and prevent unnecessary criminalization of public officials.